What lean is really about: Malaysian automotive perspective - Islam, A. S. M. Touhidul; Sorooshian, Shahryar; Shariman, Mustafa (Blue Eyes Intelligence Engineering & Sciences Publication, 2018)
With the tremendous advancement of lean, it has evolved a lot. Many authors have tried to express true nature of lean invarious ways. But still it remains incomplete and ambiguous that it is possible to create a versatile but easily understandable and acceptably meaningful definition. Specially, lean is recommended to be practiced and followed by adapting it to the currentoperational and cultural status and future requirements of the specific industry. So,the author has interviewed 16 lean experts from different key functional areas in a renowned Malaysian automotive industry, and based on the analysis of qualitative dataand information received from them, proposed a new definition of lean. With clear fundamental understanding, the journey of lean is expected to be more effective, efficient and sustainable to maximize productivity and quality with lower cost and time spent in any organization.